2017
DOI: 10.3389/fnagi.2017.00227
|View full text |Cite
|
Sign up to set email alerts
|

Microglia Responses in Acute and Chronic Neurological Diseases: What Microglia-Specific Transcriptomic Studies Taught (and did Not Teach) Us

Abstract: Over the last decade, microglia have been acknowledged to be key players in central nervous system (CNS) under both physiological and pathological conditions. They constantly survey the CNS environment and as immune cells, in pathological contexts, they provide the first host defense and orchestrate the immune response. It is well recognized that under pathological conditions microglia have both sequential and simultaneous, beneficial and detrimental effects. Cell-specific transcriptomics recently became popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
59
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 117 publications
(188 reference statements)
0
59
0
Order By: Relevance
“…However, recent studies have also found that the functional effects of microglia activation are much more complex than assumed and are age and context‐dependent (Chen et al, ; Stetler et al, ). In aging or pathological conditions where chronic inflammation is predominant, microglia tend to polarize to a more destructive phenotype as exhibited in AD and other situations (Cherry et al, ; Hirbec et al, ; Parisi et al, ; Wang, Tan, Yu, & Tan, ). Thus, strategies to boost anti‐inflammatory biased phenotype while inhibiting the pro‐inflammatory phenotype may have a profound potential for effective treatment (Cherry et al, ; McGeer & McGeer, ; Wes et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, recent studies have also found that the functional effects of microglia activation are much more complex than assumed and are age and context‐dependent (Chen et al, ; Stetler et al, ). In aging or pathological conditions where chronic inflammation is predominant, microglia tend to polarize to a more destructive phenotype as exhibited in AD and other situations (Cherry et al, ; Hirbec et al, ; Parisi et al, ; Wang, Tan, Yu, & Tan, ). Thus, strategies to boost anti‐inflammatory biased phenotype while inhibiting the pro‐inflammatory phenotype may have a profound potential for effective treatment (Cherry et al, ; McGeer & McGeer, ; Wes et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Microglia, accounting for about 5–12% of all glial cells, are the first line defense of the central nervous system (Greter & Merad, ; Hirbec, Noristani, & Perrin, ; Parisi, Napoli, Pelegrin, & Volonte, ). Although more complicated functional heterogeneity is being discovered recently, microglia activation is mainly categorized into two states: the pro‐inflammatory neurotoxic state and the anti‐inflammatory neuroprotective state (Cunningham, ; Greter & Merad, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genome-wide transcriptional profiling has also been used to decipher the transcriptional remodeling that occurs during reaction, by studying various mouse models of brain diseases, such as multiple sclerosis, Amyotrophic lateral sclerosis, and Alzheimer's disease (reviewed in Hirbec, Noristani, & Perrin, 2017). These studies provided insights into the radical modifications that reactive microglia undergo in disease states (Holtman et al, 2015), and revealed the highly dynamic behavior of microglial transcriptomes at different stages of progressive neurodegenerative diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Alzheimer's disease is a chronic neurodegenerative disorder characterized by progressive and irreversible cognitive decline . Clinically, AD is characterized by early memory deficits followed by a decline in cognitive functions .…”
mentioning
confidence: 99%